Hypnotic Discontinuation Using a Blinded (Masked) Tapering Approach: A Case Series - Fung, Constance H.; Martin, Jennifer L.; Alessi, Cathy; Dzierzewski, Joseph M.; Cook, Ian A.; Moore, Alison; Grinberg, Austin; Zeidler, Michelle; Kierlin, Lara (Frontiers in Psychiatry, 2019)
Chronic use of hypnotic medications such as benzodiazepines is associated with adverse consequences including increased risk of falls. Efforts to help patients discontinue these medications have had varying levels of success. We developed a blinded (masked) tapering protocol to help patients taper off hypnotics. In this blinded protocol, patients consented to a drug taper but agreed to forego knowledge about the specific tapering schedule or the actual dose each night until the end of the taper. Blinded tapering aims to reduce negative expectancies for withdrawal effects that may impair a patient’s successful discontinuation of hypnotics. In preparation for a randomized trial, we tested the feasibility of adding a blinded tapering component to current best evidence practice (supervised hypnotic taper combined with cognitive behavioral therapy for insomnia [CBTI]) in 5 adult patients recruited from an outpatient mental health practice in Oregon. A compounding pharmacy prepared the blinded capsules for each patient. During the gradual blinded taper, each participant completed CBTI. Measures collected included feasibility/process (e.g., recruitment barriers), hypnotic use, the Dysfunctional Beliefs and Attitudes about Sleep Scale, Insomnia Severity Index, Epworth Sleepiness Scale, and Patient Health Questionnaire-9 (depressive symptoms). The intervention was feasible, and participants reported high satisfaction with the protocol and willingness to follow the same treatment again. All five participants successfully discontinued their hypnotic medication use post-treatment. Dysfunctional beliefs/attitudes about sleep and insomnia severity improved. Blinded tapering is a promising new method for improving hypnotic discontinuation among patients treated with a combination of hypnotic tapering plus CBTI.